You ask (Journal of Parents and Teachers, 2026)
It offers guidance for parents facing everyday problems with their children. It addresses the fear of failing as a parent and the impact of foul language in the family environment. It is essential reading for turning tensions at home into a more understanding and less rigid relationship.
Keywords: Family, parenting, relationships, and problems.